Metachronous Rapidly-Growing Papillary Type 2 Renal Cell Carcinoma following Contralateral Clear Cell Renal Cell Carcinoma Diagnosis – A Case Report from the Radiologic Point of View - Ben, Caspy; Kenigsberg, Konstantin; Alex, Pavlov; Natalia, Goldberg (Archives of Clinical and Medical Case Reports, 2024)
Papillary Renal Cell Carcinoma Type 2 (PRCC2) is a relatively rare aggressively- behaving tumor associated with poor prognosis. We present the case of a 74 year- old patient who underwent a unilateral radical nephrectomy 9 months prior due to a grade 4 clear cell renal cell carcinoma diagnosis, which had a newly formed 20mm renal mass suspected as malignant incidentally found during a routine MRI which was not evident in a CT scan 4 months before. This report follows the diagnostic process, radiological findings, and management in the unique case of the relatively rare rapidly progressing metachronous malignancy from the radiologic point of view, discussing the challenges of diagnosis and clinical staging affecting the patient’s outcome.